PENGARUH KOMITMEN ORGANISAIONAL, KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN KANTOR CAMAT LOWOKWARU KOTA MALANG - Wilda Maghfiroh; Hadi Sunaryo; Muhammad Khoirul (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT The study was conducted in subdistrict head’s office Lowokwaru, Malang. The purpose of this study was to examine and and analyze the influence of organization’s commitment, work’s satisfaction and motivation to employee performance partially or simultaneously. The sample used are whole employee of subdistrict head’s office Lowokwaru, Malang much as 32 employees. Collection data method used was a questionnaire. The analysis includes instruments test, normality test, classic assumption test, linear regression test, hypothesis test and coefficient determination test using multiple linear regression analysis with SPSS 14.0 for Windows. The result showed that organization’s commitment and work’s satisfaction partially has an influence positively and motivation has an influence negatively to the employee’s performance of subdistrict head’s office Lowokwaru, Malang, organization’s commitment, work’s satisfaction and motivation simultaneously have an influence to the employee’s performance of subdistrict head’s office Lowokwaru, Malang. Keywords: organization’s commitment, work’s satisfaction, motivation,employee’s performance.